The Metabolic Chemical Reporter Ac46AzGal Could Incorporate Intracellular Protein Modification in the Form of UDP-6AzGlc Mediated by OGT and Enzymes in the Leloir Pathway - Wang, Jiajia; Dou, Biao; Zheng, Lu; Cao, Wei; Dong, Peiyu; Chen, Yingyi; Zeng, Xueke; Wen, Yinhang; Pan, Wenxuan; Ma, Jing; Chen, Jingying; Li, Xia (Frontiers in Chemistry, 2021)
Galactose is a naturally occurring monosaccharide used to build complex glycans that has not been targeted for labeling as a metabolic reporter. Here, we characterize the cellular modification of proteins by using Ac46AzGal in a dose- and time-dependent manner. It is noted that a vast majority of this labeling of Ac46AzGal occurs intracellularly in a range of mammalian cells. We also provided evidence that this labeling is dependent on not only the enzymes of OGT responsible for O-GlcNAcylation but also the enzymes of GALT and GALE in the Leloir pathway. Notably, we discover that Ac46AzGal is not the direct substrate of OGT, and the labeling results may attribute to UDP-6AzGlc after epimerization of UDP-6AzGal via GALE. Together, these discoveries support the conclusion that Ac46AzGal as an analogue of galactose could metabolically label intracellular O-glycosylation modification, raising the possibility of characterization with impaired functions of the galactose metabolism in the Leloir pathway under certain conditions, such as galactosemias.